Meningkatkan Motivasi Belajar Menulis Huruf Dengan Benar Pada Siswa Kelas I SD Negeri 012 Rambah Melalui Metode Latihan - Angela Samosir (Indonesian Journal of Basic Education, 2018)
This study aims to improve students' writing skills, through the application of thickening letters techniques. This technique is one form of classical learning development which has the characteristics of developing the activity of writing letters correctly through continuous training (continuous). Research subjects were students of grade 1 elementary school no. 012 Pasir Baru Village, Rambah Subdistrict, Rokan Hulu Regency, 2016-2017 School Year (T / P). The research approach used is quality while the type of research is Classroom Action Research (CAR). This study uses 3 rounds of classroom action (Pre-cycle, Cycle I and Cycle II. Each round consists of four stages: Planning, Implementation, Observation and Reflection. Data analysis techniques using interactive model analysis techniques consisting of three components, namely: data reduction , data presentation and conclusion drawing.Based on the results of the research that has been carried out it can be concluded that through the technique of thickening the letters can improve students 'writing skills in grade 1 Public Elementary School No. 012 Rambah.This can be seen from the increase in percentage percentage of students' completeness in initial conditions of which only 35% increased to 73% in the first cycle and reached 96% at the end of the second cycle, the total completeness was 61%, the average achievement in the 60-point pre-cycle increased to 74 points in the first cycle and 87 points. at the end of the second cycle, the total increase was an average of 27 points